Karakteristik Bahasa Inggris Maritim Secara Kata dan Frasa - Aprillina Aprillina; Dhanan Abimanto (Asosiasi Periset Bahasa Sastra Indonesia, 2023)
English is an international language used in various fields, including the maritime sector. In the maritime sector, English is used for communication, both between seafarers and between seafarers and related parties, such as port officers, cargo agents and shipping companies. In order to provide competent resources in the maritime world, the role of maritime vocational education is present to address these problems. In Indonesia, maritime vocational education aims to produce graduates who have competence in the maritime field. One of the competencies that maritime vocational education graduates must have is the ability to speak maritime English. In order to provide competent resources in the maritime world, the role of maritime vocational education is present to address these problems. Although the importance of maritime English is recognized, there is a gap between industry needs and the competencies of Indonesian maritime vocational education graduates. Mastery of correct maritime terminology is essential for sailors and maritime personnel. Maritime terms used incorrectly can lead to potentially dangerous misunderstandings. Maritime jargon is often used in oral and written communication in the maritime environment. Maritime jargon is usually used to convey messages briefly and clearly.